Development of a pH sensitive nanocarrier using calcium phosphate coated gold nanoparticles as a platform for a potential theranostic material - Cha, Eui-Joon; Sun, In-Cheol; Lee, Sang Cheon; Kim, Kwangmeyung; Kwon, Ick Chan; Ahn, Cheol-Hee (SPRINGER, 2012)
Methoxy-poly(ethylene glycol) (mPEG)-Asp-Cys was synthesized by ring opening polymerization, and its characterization by 1H nuclear magnetic resonance (NMR) showed that the copolymer has 18 aspartic acid units and 0.95 cysteine units on average, with the molecular weight and distribution of 13.1 k and 1.15. PEGylated AuNP with doxorubicin containing CaP layers was prepared to have the size of 79.8 +/- 18.7 nm by light scattering measurement method, with the CaP thickness around 27 nm. PEGylated Dox-AuNP@CaP was stable in the physiological conditions for several weeks in the presence of glutathione. Loading amount and efficiency of doxorubicin into the particles were 1.3% and 27.9%, respectively. The loading amount was 1.3%, lower than common organic selfassembled carriers, because of the relatively high atomic mass of gold. In vitro release experiments were performed in two different environments: extracellular fluid (pH 7.4) and intracellular lyosomal fluid (pH 4.5). The amount of released doxorubicin from PEGylated Dox-AuNP, without CaP layer, exceeds 60% in 2 h. In contrast, PEGylated Dox-AuNP@CaP effectively limited the doxorubicin release in the extracellular condition to 13% after 12 h, and changing the media to the intracellular lysosomal condition resulted in a triggered release of doxorubicin from 7% to 78% in an additional 4 h. Cell viability of PEGylated Dox-AuNP@CaP and PEGylated AuNP@CaP were estimated with HeLa cells by MTT assay. Cell viability of PEGylated Dox-AuNP@CaP came down to 19% after 24 h incubation, while the PEGylated AuNP@CaP particle itself showed slight cytotoxicity with the same conditions. The prepared PEGylated Dox-AuNP@CaP worked as a pH- and ion concentration-sensitive drug-delivery system as well as theranostic nanoparticles for CT imaging and cancer treatment.
Keywords: IRON-OXIDE NANOPARTICLES; IN-VIVO; MAGNETIC-RESONANCE; MICELLAR NANOPARTICLES; CONTRAST AGENTS; DRUG-DELIVERY; IMAGING PROBE; CANCER; FLUORESCENCE; DIAGNOSIS